THE ROLE OF TECHNOLOGY IN TEACHING PRONUNCIATION AMONG PRIMARY SCHOOL LEARNERS - Yokubjonova Mahliyo Akramjon qizi, (Ustozlar uchun, 2025)
This study explores the role of technology in enhancing pronunciation skills among primary school learners. With the growing integration of digital tools in education, pronunciation instruction has evolved beyond traditional methods to include interactive software, mobile applications, speech recognition systems, and multimedia resources. This paper examines how these technologies support young learners in acquiring accurate pronunciation through immediate feedback, engaging interfaces, and individualized learning paths. Drawing on recent research and classroom practices, the study highlights the effectiveness of technology in increasing learner motivation, improving listening and speaking accuracy, and promoting autonomous learning. The findings suggest that when appropriately implemented, technological tools can significantly enhance pronunciation teaching in primary education, making it more effective, inclusive, and enjoyable for both teachers and students.